Are patient surveys valuable as a service-improvement tool in health services? An overview - Patwardhan A; Spencer CH (Dove Medical Press, 2012)
Anjali Patwardhan,1 Charles H Spencer21Nationwide Children’s Hospital Columbus, 2Ohio State University, Columbus, OH, USAAbstract: Improving the quality of care in international health services was made a high priority in 1977. The World Health Assembly passed a resolution to greatly improve “Health for all” by the year 2000. Since 1977, the use of patient surveys for quality improvement has become a common practice in the health-care industry. The use of surveys reflects the concept that patient satisfaction is closely linked with that of organizational performance, which is in turn closely linked with organizational culture. This article is a review of the role of patient surveys as a quality-improvement tool in health care. The article explores the characteristics, types, merits, and pitfalls of various patient surveys, as well as the impact of their wide-ranging application in dissimilar scenarios to identify gaps in service provision. It is demonstrated that the conducting of patient surveys and using the results to improve the quality of care are two different processes. The value of patient surveys depends on the interplay between these two processes and several other factors that can influence the final outcome. The article also discusses the business aspect of the patient surveys in detail. Finally, the authors make future recommendations on how the patient survey tool can be best used to improve the quality of care in the health-care sector.Keywords: patient surveys, quality improvement, service gaps